Effect of verbal counselling on metred‐dose inhaler proper use and lung function test amongst asthmatic patients: A meta‐analysis. Issue 6 (15th February 2021) - Abdelrahman, Mona A.; Saeed, Haitham; Osama, Hasnaa; Harb, Hadeer S.; Madney, Yasmin M.; Abdelrahim, Mohamed E. A.
Abstract: Introduction: The main cause of poor asthma control is mostly related to the inability of the asthmatic subjects to use their metred‐dose inhaler (pMDI) correctly. The present study aimed to evaluate the role of contentious pMDI verbal‐counselling on the pMDI inhalation technique and pulmonary functions of asthmatics. Methods: Through a systematic literature search up to December 2020, 10 studies with 1937 asthmatic subjects, who had at least two pMDI inhalation technique verbal counselling sessions (visits), were identified reporting relationships between contentious pMDI verbal counselling, and the number of inhalation technique mistakes and lung functions score. Mean difference (MD) with 95% confidence intervals (CIs) was calculated comparing counselling visits results using the continuous method with a random effect model. Results: Visit 1 had a significantly higher mean number of mistakes compared with visit 2 (MD, 19.98; 95% CI, 11.54‐28.41, P  < .001); Also, visit 2 had a significantly higher mean number of mistakes compared with visit 3 (MD, 12.17; 95% CI, 9.31‐15.02, P  < .001). The extent of improvement in the inhalation technique was higher between visits 1 and 2 compared with that between visits 2 and 3. The impact of continuous verbal counselling was also observed on the forced expiratory volume in one second as percentage of vital capacity [(MD, −5.56; 95% CI, −6.50 to −4.61, P  < .001) between visits 1 and 2 and (MD, −6.40; 95% CI, −7.71 to −5.10, P  < .001) between visits 2 and 3] and the peak expiratory flow rate [(MD, −11.47; 95% CI, −18.73 to −4.22, P  < .001) between visits 1 and 2 and (MD, −16.53; 95% CI, −25.80 to −7.26, P  < .001) between visits 2 and 3]. The extent of improvement in lung functions was similar between visits 1 and 2 and visits 2 and 3. Conclusion: Based on this meta‐analysis, Continuous pMDI verbal counselling, at every possible opportunity, is a must since lung functions and pMDI inhalation technique improvements were observed with continuous pMDI verbal counselling.